Pengaruh Atribut Produk Dan Harga Terhadap Kepuasan Konsumen Roti Bakar 88 - Susi Riswani Banjarnahor; Sri Yuniati P.K Hardini; Abel Gandhy; Febri Budiman (Jurnal Ilmiah Manajemen Kesatuan, 2022)
Toast is one of the popular food Indonesia. Roti Bakar 88 is an outlet that sell ready to eat toast. Business trends show there is a change in the focus of the business that initially focuses on the product to be consumer-focused. For this reason, consumer satisfaction is an interesting topic to study. The purpose of the research is to analyze the impact of product atributte and price performance on consumer satisfaction in Roti Bakar 88. Data collected using questionare consists of 100 respondens. Data was analyzed using multiple linier regression method. The result shows that, product attributte and price variable is partially significant influenct the consumers satisfaction. The results also tells that independent variable significantly influenct independent variable simultaneously. Owner of Roti Bakar 88 need to improve the performance product features which consists of product information and packaging through include information on the nutritional value contained and benefits that consumer get. While the dimension of product quality, logo design maintened or improve because consumer already satisfied. Roti Bakar 88 has a price that is in the range of < Rp. 50.000, where the consumer are satisfied with the price. The price is still affordable for all consumer.When product attributes and prices can meet consumer expectations, customer satisfaction of Roti Bakar 88 will increase. Consumers are also satisfied with the price provided, because feel it appropriate with product quality and service provide.